Euro-myth: nationalism, war and the legitimacy of the European Union. Issue 2 (2nd April 2016) - Wellings, Ben; Power, Ben
Abstract : This article engages with Montserrat Guibernau's argument about the 'non-emotional' nature of European identity. In critiquing this argument, this article also advances a broader argument of its own: that we are witnessing an emergent European nationalism. The article suggests that although there are few people who passionately defend European integration today, those that do are increasingly resorting to arguments that depend simultaneously on invoking and rejecting collective memories of intra-European conflict derived from the 'emotive' period of European integration in the 1940s to shore up the increasingly challenged legitimacy of the European Union today in its hour of greatest crisis.